2013
DOI: 10.1002/srin.201200283
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model of the Solid Flow Behavior in a Real Dimension Blast Furnace: Effects of the Solid Volume Fraction on the Velocity Profile

Abstract: A mathematical model based on the continuum mechanic concept has been developed to describe the profile of solid particles in a blast furnace with respect to the in-furnace conditions and characteristics, e.g., the shape and size of the deadman. The Navier-Stokes differential equation for multi-phase multi-dimensional space has been used to describe the behavior of existing phases. The equation has been modified to make it possible to describe the dual nature of the solid phase in the system by applying the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A comparison study with results reported 8) in the literature verifying the functionality is reported in a related paper. 37) In the future there might also be a possibility to validate the model using actual data from the experimental furnace hosted by Swerea MEFOS AB.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison study with results reported 8) in the literature verifying the functionality is reported in a related paper. 37) In the future there might also be a possibility to validate the model using actual data from the experimental furnace hosted by Swerea MEFOS AB.…”
Section: Introductionmentioning
confidence: 99%